2020
DOI: 10.1016/j.cdtm.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathogenesis of Peyronie's disease: A narrative review

Abstract: Peyronie’s disease (PD) is a benign, progressive fibrotic disorder characterized by scar or plaques within the tunica albuginea (TA) of the penis. This study provides new insights into the pathogenesis of PD based on data from different studies regarding the roles of cytokines, cell signaling pathways, biochemical mechanisms, genetic factors responsible for fibrogenesis. A growing body of literature has shown that PD is a chronically impaired, localized, wound healing process within the TA and the Smith space.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 143 publications
1
24
0
4
Order By: Relevance
“…Furthermore, we have detected a significant increase in the microvessel and arteriole density in the contracted M-side of the relapsed clubfoot tissue, which was connected to an increase in pro-angiogenic factors 8 . These pathways are identical with those described in other fibroproliferative and angioproliferative diseases, such as Dupuytren’s contracture and Peyronie’s disease 9 , 10 .…”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, we have detected a significant increase in the microvessel and arteriole density in the contracted M-side of the relapsed clubfoot tissue, which was connected to an increase in pro-angiogenic factors 8 . These pathways are identical with those described in other fibroproliferative and angioproliferative diseases, such as Dupuytren’s contracture and Peyronie’s disease 9 , 10 .…”
Section: Introductionsupporting
confidence: 79%
“…Previous articles investigated the effects of iNOS silencing in mice, thereby confirming its anti-fibrotic effect and highlighting its significance in protecting smooth muscle cells (SMCs) of corpus cavernosum ( Ferrini et al., 2010 ). Depending on animal model, iNOS and hypoxia-inducible factor–1 (HIF-1) were upregulated in PD-like lesions ( Krakhotkin et al, 2020 ). Therefore, inhibiting the expression or the product activity of hypoxia-inducible profibrotic gene may be an exciting supplement to PD treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the iNOS knockout mouse have confirmed the anti-fibrotic role of iNOS and emphasized the importance of iNOS in protecting SMCs in the penile corpora cavernosa ( Ferrini et al, 2010 ). Moreover, an animal study also found that the levels of iNOS and hypoxia-inducible factor-1 (HIF-1) rise in PD-like lesions ( Krakhotkin et al, 2020 ). Thus, the inhibition of profibrotic gene expression or activity might be an exciting addition to PD therapy in future.…”
Section: Molecular Mechanismsmentioning
confidence: 99%